Kualitas Fisik dan Sensoris Daging Ayam Broiler yang Diberi Pakan dengan Penambahan Ampas Virgin Coconut Oil (VCO) (Physical and Sensory Quality of Meat of Broiler Chicken Fed with The Addition of Virgin Coconut Oil Waste) - Agus Hadi Prayitno; Edi Suryanto; Zuprizal (Zuprizal) (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The experiment was conducted to evaluate physical and sensory quality of meat of broiler chicken fed diets with addition of VCO waste. One hundred and twenty five DOC’s unsex Arbor Acres strain CP 707 were randomly dividedinto 25 groups containing five birds each. There were five dietary treatments and five cages in each treatment for replication. Chickens were raised for 35 days. Levels of VCO waste in feed treatments were: 0, 0.5, 1.0, 1.5, and 2.0%.Drinking water and feed were given ad libitum. For the first week, birds were fed BR1, afterward dietary treatments were given until the end of the experiment and then they were slaughtered. Meat samples (Pectoralis superficialis) weretaken to determine the physical and sensory quality of meat. The data of physical quality were analysed by the analysis variance of completely randomized design, whereas data of sensorial quality were analysed by the analysis of nonparametric test of Hedonic Kruskal-Wallis. The results showed that addition of VCO waste level increased pH value and water-holding capacity and decreased cooking loss and tenderness of meat of broiler chicken. However, sensorialtest indicated that VCO waste addition did not affect color, taste, texture, juiciness, tenderness, and acceptability of meat of broiler chicken. It could be concluded that the addition of VCO waste in the ration improved the physicalquality of broiler meat.(Key word: Chicken broiler meat, Physical quality, Sensory, VCO waste)